Effects of Cornus mas L. on lipid peroxidation and anti-oxidative enzyme activity in high fat diet fed rats - KARĞIN, DİCLE; YAVUZ, AYŞE NUR; ÇAM, MUHAMMET EMİN; AKTAÇ, ŞULE (My University, 2023)
Cornelian cherry (Cornus mas L.) has been used for centuries as a traditional herbal medicine in Europe and Asia. In this study, we aimed to describe the effect of Cornus mas L. (C. mas) on the activity of the antioxidant enzymes and a detoxification agent in rats fed a high-fat diet. Forty-eight adult Sprague Dawley rats were randomly assigned to six groups of eight animals each: Standard diet (Control), High Fat Diet (HFD), HFD + C. mas (200 mg/kg/day; 8 weeks), HFD + Atorvastatin (20 mg/kg/day; 8 weeks), HFD post-treated with C. mas (200 mg/kg/day; 4 weeks), HFD posttreated with Atorvastatin (20 mg/kg/day; 4 weeks). The activity of the antioxidant enzymes, Superoxide dismutase (SOD), Catalase (CAT), Glutathione peroxidase (GPx), detoxification agent glutathione (GSH), and oxidative stress parameter thiobarbituric acid reactive substances (TBARS) were measured in the liver tissues. GPx, SOD, and CAT enzyme levels were decreased in HFD groups compared to the control (p < 0.05). However, Cornus mas L. promoted antioxidant activity by increasing GPx, SOD, and CAT enzymes and It also reduced oxidative stress (as an increase in GSH) both in the HFD + C. mas group and the HFD post-treated C. mas group compared to the HFD group (p < 0.05). Our study showed that feeding a high-fat diet increases oxidative stress. Cornus mas L treatment improves antioxidant enzyme activity and oxidative stress parameters in the liver tissues of rats.
Keywords: Beslenme ve Dietetik; Sağlık Bilimleri; Nutrition and Dietetics; Health Sciences; Tarım ve Çevre Bilimleri (AGE); Klinik Tıp (MED); Tarım Bilimleri; BESLENME VE DİYETETİK; Agriculture & Environment Sciences (AGE); Clinical Medicine (MED); AGRICULTURAL SCIENCES; NUTRITION & DIETETICS; Beslenme ve Diyetetik; Cornus mas L.; liver; antioxidant; glutathione; high-fat-diet